2021
DOI: 10.4102/phcfm.v13i1.2723
|View full text |Cite
|
Sign up to set email alerts
|

Exploring opportunities to enhance effectiveness of mobile health and nutrition strategy for providing health and nutrition services amongst pastoralists in Somali region, Ethiopia

Abstract: Background: The health system in Ethiopia’s Somali Region is weak with limited number of health facilities with more than 60% of the population living more than 5 km to the nearest health facilities. The deployment of mobile health and nutrition teams has played critical role in providing essential health and nutrition services.Aim: This study aimed to assess the effectiveness of the mobile health and nutrition strategy in providing health and nutrition services in the targeted woredas (districts).Setting: Som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 16 publications
2
9
0
Order By: Relevance
“…The odds of under-five mortality were higher for residents of Afar and Somali regions compared to the Tigray region. This coincides among other things, with Somali and Afar regions having the first and second lowest coverage of children with all basic as well as second and first prevalence respectively [ 35 , 36 ]. Additionally, the Somali region was one of the regions that were in the primary cluster from our spatial scan statistics analysis where under-five mortality is more likely to occur.…”
Section: Discussionmentioning
confidence: 65%
“…The odds of under-five mortality were higher for residents of Afar and Somali regions compared to the Tigray region. This coincides among other things, with Somali and Afar regions having the first and second lowest coverage of children with all basic as well as second and first prevalence respectively [ 35 , 36 ]. Additionally, the Somali region was one of the regions that were in the primary cluster from our spatial scan statistics analysis where under-five mortality is more likely to occur.…”
Section: Discussionmentioning
confidence: 65%
“…The finding is consistent with another study which showed that MHNT program is documented as a convenient approach of health service delivery in the pastoral areas of Ethiopia. 19 In another study it has been also reported that the opinion of the society about the usefulness of the MHNT approach is entirely encouraging. 18…”
Section: Discussionmentioning
confidence: 91%
“…This finding corroborates with a study by Olaji et al which reported that movement restrictions affected the successful implementation of MHNT programs in pastoral areas. 19 This implies that the pastoral lifestyle and their movement pattern should be considered for appropriate design and implementation of effective MHNT strategy in the local context.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past decade, the WHO open-source AccessMod software has often been used to model geographic accessibility coverage of various types of health services (11)(12)(13)(14)(15). To analyze the accessibility coverage of a country or region, AccessMod applies a least-cost path algorithm to compute the routes with the shortest travel time between any location and the nearest health service, for example an EmONC facility (10,16).…”
Section: Knowledge Elicitation Travel Scenario Workhopsmentioning
confidence: 99%